2012
DOI: 10.4236/aim.2012.23033
|View full text |Cite
|
Sign up to set email alerts
|

Development of Efficient Fermentation Process at Bioreactor Level by Taguchi's Orthogonal Array Methodology for Enhanced Dextransucrase Production from <i>Weissella confusa</i> Cab3

Abstract: The influence of medium ingredients on extracellular dextransucrase production by a new bacterial strain Weissella confusa Cab3 (Genbank Accession Number JX649223) was evaluated using fractional factorial design of Taguchi's orthogonal array. Four metabolism influencing factors viz. sucrose, yeast extract, K 2 HPO 4 and Tween80 were selected to optimize dextransucrase production by W. confusa Cab3 using fractional factorial design of Taguchi methodology. Based on the influence of interaction components of ferm… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2013
2013
2022
2022

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 7 publications
(1 citation statement)
references
References 19 publications
0
1
0
Order By: Relevance
“…Landon [28] studied effect of stirring on dextransucrase production for Leuconostoc mesenteroides NRRL B512 (F) and suggested some limitations in difussion through cell membrane in static culture. Recently, dextransucrase production by a new bacterial strain Weissella confusa Cab3 was scaled up in lab scale bioreactor resulting in further enhancement of enzyme activity (22.0 U/ml) than shake flask level of 17.54 U/ml [29].The dextransucrase activities in excess of 21.9 U/ ml have also been obtained by culturing L. mesenteroides NRRL B512(F) under non-aerated fed-batch fermentation conditions [30]. However, Santos et al, [20] found that aeration does not have an important effect in fermentation by L. mesenteroides NRRL B512(F).…”
Section: Course Of Fermentation By Acetobacter Tropicalis For the Promentioning
confidence: 99%
“…Landon [28] studied effect of stirring on dextransucrase production for Leuconostoc mesenteroides NRRL B512 (F) and suggested some limitations in difussion through cell membrane in static culture. Recently, dextransucrase production by a new bacterial strain Weissella confusa Cab3 was scaled up in lab scale bioreactor resulting in further enhancement of enzyme activity (22.0 U/ml) than shake flask level of 17.54 U/ml [29].The dextransucrase activities in excess of 21.9 U/ ml have also been obtained by culturing L. mesenteroides NRRL B512(F) under non-aerated fed-batch fermentation conditions [30]. However, Santos et al, [20] found that aeration does not have an important effect in fermentation by L. mesenteroides NRRL B512(F).…”
Section: Course Of Fermentation By Acetobacter Tropicalis For the Promentioning
confidence: 99%